Analisis Persepsei Mengenai Pembelajaran Skripsi pada Followers @Buiramira - Iffah Ulya Salsabila; Widia Febrianti; Rifan Kurniawan; Yohanes Arie Kuncoroyakti (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2026)
In today’s digital era, social media has become a new space for individuals to develop their personal creativity. This study analyzes the content strategy of the TikTok account @buiramira in building audience engagement and understanding the impact it has on the account’s image. The background of this research stems from the phenomenon of increasing social media usage, particularly TikTok, as a means of communication, entertainment, and promotional media. Using McGuire’s information processing theory, the study finds that followers’ perceptions of the TikTok account @buiramira as a source of information for thesis learning are very positive, making it suitable as a learning platform. The content presented not only provides technical knowledge but also shapes students’ attitudes and behaviors in facing the thesis process.This research employs a descriptive qualitative method  with data collection techniques including content observation, interviews, and documentation. The results show that the @buiramira account successfully builds strong interaction with its audience through consistent uploads, the use of a communication style that feels close to viewers, and the utilization of current trends. In addition, the study finds that audience engagement is strongly influenced by a combination of content creativity, relevant topic selection, and the account owner’s ability to maintain emotional closeness with followers. These findings emphasize the importance of well-planned digital communication strategies in managing social media accounts, so that they can provide benefits both personally and professionally.